American Attitudes towards Islam - The John Zogby Group International, Inc. (International Institute of Islamic Thought, 1993)
Introduction and Methodology The American Muslim Council poll was conducted from 16-23 Mamh 1993 by the John Zogby Group International, Inc., of New Hartfod, New York. A total of 905 adults were contacted by telephone by trained canvassers from the Zogby Group offices. The random sample was stmtified to ensure a equitable distribution of Fespondents by region. The sample was selected by a ptocectUre of random digiting in order to give listed and unlisted residential numbers an equal chance of selection All area codes in the contiguous forty-eight states were mpmented, and each state was represented in the total sample accotding to its proportion of the total population. Calls wee made from 4:OO pm to 9:OO pm in all time zones on weeknights, from 1O:OO am to 5:OO pm on Saturday, and from 5:OO pm to 9:OO pm on Sunday. Three callbacks were made to each household where there was no initial contact. Sample characteristics are described below: ...